Analisis Semiotika Dalam Puisi “Tak Sepadan” Karya Chairil Anwar Menggunakan Teori Ferdinand De Saussure - Suge, Firnawati; Gaga, Diva Kirana; Ali, Ayu Hidayanti (Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study aims to reveal the semiotic meaning in the poem Tak Sepadan by Chairil Anwar using Ferdinand de Saussure’s theory. The poem was chosen due to its rich symbols and signs that depict emotional conflict and inequality in love. Saussure’s semiotic approach, which divides signs into two main components: the signifier and the signified, is applied to systematically analyze the linguistic relations within the poem. The research method employed is descriptive qualitative with a textual analysis technique. Data were collected through in-depth reading and identification of linguistic signs functioning as signifiers, then interpreted for their signified meanings. The analysis results show that Tak Sepadan contains profound meanings about alienation, suffering, and imbalance in love expressed through symbols such as “Ahasvéros,” “blind wall,” and “the burning fire.” These signifiers form signified concepts that portray the inner torment and marginalization of the poem’s “I” persona. The conclusion confirms that Ferdinand de Saussure’s semiotic theory is effective in uncovering latent layers of meaning in poetry, especially in analyzing linguistic signs that construct the emotional and philosophical messages of Chairil Anwar. This study also contributes to the development of literary and semiotic studies in the context of modern Indonesian poetry.